Design and analysis of the cold cathode ion source for 200 MeV superconducting cyclotron. (November 2019) - Xu, S.W.; Chen, G.; Xu, M.M.; Karamyshev, O.; Karamyshev, G.; Shirkov, G.; Calabretta, L.
Abstract: SC200 is a superconducting isochronous cyclotron which generates 200 MeV, 400 nA proton beam for particle therapy. The cold-cathode-type Penning ion gauge (PIG) ion source for the internal ion source of SC200 has been selected as an alternative and preliminary designed. In this paper, design of ion source and test bench are demonstrated. Currently, the properties of ion source have been simulated for a variety of electric field and magnetic field distributions. The secondary electron emission in electromagnetic field has been simulated. It provides reference for the optimization design of arc chamber. In addition, the sample of cold-cathode-type ion source has been tested on the test bench and extracted beam intensity has been measured over 200 μ A.